SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN CALON KARYAWAN PADA SUZUYA ROCKY PLAZA PADANG - Jab, Rajab Jab (JURNAL AKADEMIKA, 2017)
Abstract - A decision suporting system (SPK) is a system information of computer based. it provides and designs of information that is used by the manager in taking decision process. this system holds on Suzuya Rocky Plaza Padang in recruitmen processing. These problems that can be found are: the difficulties to determine the candidate of employee who is really able to do the job in the position provided. the number of turn over employees is very high caused of resignation of employees who have received. then, Unavailability of applications that can assist Human Resource Development (HRD) in processing the assessment of required employee criteria.The aim of this research helps the Human Resource Development (HRD) in accepting of the employee, Minimize employee turnover to determine the quality of employees that is received.  Based on the cases above, decision suporting system is the prominent way to used for Employees recruitement at Suzuya Rocky Plaza. The result shows that those applications can help the HRD in giving assesment to the employee candidate who will be received. Keyword: decision suporting system, recruitment